2015
DOI: 10.1073/pnas.1503190112
|View full text |Cite
|
Sign up to set email alerts
|

Changing central Pacific El Niños reduce stability of North American salmon survival rates

Abstract: Pacific salmon are a dominant component of the northeast Pacific ecosystem. Their status is of concern because salmon abundance is highly variable-including protected stocks, a recently closed fishery, and actively managed fisheries that provide substantial ecosystem services. Variable ocean conditions, such as the Pacific Decadal Oscillation (PDO), have influenced these fisheries, while diminished diversity of freshwater habitats have increased variability via the portfolio effect. We address the question of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
126
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 41 publications
11
126
0
Order By: Relevance
“…Regardless of salmon biomass, predicted total scale size was positively associated with increases in NPGO. Changes in observed total scale size were associated with changes in NPGO, particularly when PDO was negative, reflecting cooler sea surface temperatures (Mantua and Hare 2002) that increased coastal primary productivity (Di Lorenzo et al 2008;Kilduff et al 2015). Metabolic costs decline when water is cooler, resulting in faster growth, especially when coupled with an increase in food availability (Farley et al 2011;Siddon et al 2013).…”
Section: Trends In Growth Biomass and Climate Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of salmon biomass, predicted total scale size was positively associated with increases in NPGO. Changes in observed total scale size were associated with changes in NPGO, particularly when PDO was negative, reflecting cooler sea surface temperatures (Mantua and Hare 2002) that increased coastal primary productivity (Di Lorenzo et al 2008;Kilduff et al 2015). Metabolic costs decline when water is cooler, resulting in faster growth, especially when coupled with an increase in food availability (Farley et al 2011;Siddon et al 2013).…”
Section: Trends In Growth Biomass and Climate Variationmentioning
confidence: 99%
“…Weakening of subpolar and subtropical gyres decreases primary productivity (Schwing et al 2002;Behrenfeld et al 2006;Di Lorenzo et al 2008) and has been associated with decreased salmon abundance (Kilduff et al 2015), growth (Wells et al 2006), and body size (Jeffrey et al 2017) due to changes in prey species (Kaeriyama et al 2004). As a result of lower metabolic costs (Farley et al 2011;Siddon et al 2013), cooler temperatures have been shown to increase the growth potential of Pacific salmonids.…”
Section: Introductionmentioning
confidence: 99%
“…Warm periods in the CCLME are characterized by sharp reductions in cool, nutrientrich, highly productive upwelled and subarctic water (Chavez et al 2002;Checkley and Barth 2009), a shift from lipid-rich to lipid-poor zooplankton (Peterson and Schwing 2003), and an inf lux of predators to the nearshore areas critical for salmon early marine survival (e.g., Pearcy 1992; Wells et al 2017). These shifts in the prey base and predator distributions favor reduced growth and survival rates for CCLME salmon (e.g., Daly et al 2017), and anomalously warm CCLME SSTs are associated with low post-release survival rates for hatchery-origin coho and Chinook salmon from southeast Alaska to California (Sharma et al 2012;Kilduff et al 2015). While links between salmon abundance (or catch) and SST are not easily evaluated with time series correlations (see online supplement material), a strong link between record-warm 2014-16 CCLME SSTs and negative impacts on the West Coast salmon fishery in 2016 is evidenced by a shift to subtropical species and widespread negative impacts (increased mortality rates, reduced reproductive success and/or abundance) on top predators like sea birds, salmon, and marine mammals that typically thrive under neutral or cool SST conditions (Cavole et al 2016;Peterson et al 2016;Welch 2016).…”
mentioning
confidence: 99%
“…Furthermore, although ENSO effects are global, there is variability in the magnitude of impact of ENSO effects, with some regions considered "teleconnected" to ENSO (i.e., they experience climatic anomalies linked to ENSO anomalies despite being many thousands of kilometers away) whereas other regions are nonteleconnected (12,14). As such, ENSO represents a useful natural experiment that may be used to infer effects of altered climatic patterns on a variety of phenomena, including conflict (12), vegetation abundance (17), health of fisheries (20), agricultural productivity (21), and infectious diseases (22).…”
mentioning
confidence: 99%